Training or Counseling for Tax of Micro, Small and Medium Enterprises and Tax Incentives During the Covid 19 Pandemic - Fuadah, Luk Luk; Dewi, Kencana; Liliana, Liliana; Saggaf, Abdullah (Faculty of Economics, Universitas Sriwijaya, 2022)
The purpose of this service is to conduct training/counseling on Micro, Small and Medium Enterprises (MSMEs) Taxes during the Covid 19 Pandemic in West Ilir District. II. This is because it is important for MSMEs owners to understand about tax incentives during the Covid 19 pandemic given by the government. The method used in this service is to conduct training/counseling through monologues and also dialogues for MSMEs from Ilir Barat II District. The place for the activity is in the Diploma III Hall, Faculty of Economics, Sriwijaya University. Implementation time is Wednesday, November 11, 2020. Participants who take part are MSME owners, including convection, culinary, souvenir and stallbusinesses. The results of this service are expected to be able to understand and know the tax incentives provided by the government that can be utilized by MSMEs. The training/counseling provides convenience for the owners of Micro, Small and Medium Enterprises (MSMEs) in Ilir Barat II District to calculate Income Tax, Value Added Tax. Next, this training/extension provides benefits and knowledge about tax incentives for Micro, Small and Medium Enterprises (MSMEs) in Ilir Barat II District. Furthermore, this training / counseling also provides insight, especially regarding tax incentives during the 2019 Corona Virus Disease (Covid) Pandemic. This kind of training or counseling is very, very important for owners of Micro, Small and Medium Enterprises (MSMEs) in Ilir Barat II District. Thus, the role of the government through the provision of tax incentives can be carried out properly in accordance with the expected goals.